Soluble SorLA in CSF, a novel biomarker to explore disrupted trafficking of SorLA protein in Alzheimer disease - Romain Castelot; Aline Zarea; David Wallon; Anne Rovelet-Lecrux; Catherine Schramm; Muriel Quillard-Muraine; Anne Beaume; Frédéric Blanc; Olivier Bousiges; Julien Dumurgier; Maïté Formaglio; Gwenael Leguyader; et al. (Alzheimer’s Research & Therapy)
Abstract Background The SorLA protein, encoded by the Sortilin-related receptor 1 (SORL1) gene, is a major player in Alzheimer’s disease (AD) pathophysiology. Functional studies demonstrated that SorLA deficiency results in increased production of Aβ peptide, and thus a higher risk of AD. SorLA can be subject to proteolytic shedding at the cell surface, leading to the release of the soluble ectodomain of the protein (sSorLA) in the extracellular space. Recently, we demonstrated that a large proportion (~25%) of rare SORL1 missense variants found in AD patients alter SorLA trafficking along the constitutive secretory pathway, resulting in reduced delivery of SorLA to the plasma membrane and thus a loss of function. Here, we aimed to determine if CSF levels of sSORLA in AD patients carrying SORL1 rare variants that impact or not the trafficking of the protein can be used as a novel biomarker to explore disrupted trafficking of SorLA protein in AD. Methods A total of 151 participants were categorized into 5 study groups: controls without any neurodegenerative disease (n=30), patients suffering from Fronto-Temporal Lobar Degeneration (FTLD, n=34), AD patients not carrying a SORL1 rare variant (AD SORL1 WT, n=40), AD patients carrying SORL1 trafficking-defective variants or a protein-truncating variant (PTV) (ADSORL1 TD, n=16), and AD patients carrying a SORL1 variant with no evidence of trafficking defect (AD SORL1 nTD, n=31). Thirty-three unique rare variants of SORL1 were included for this study: 3 PTVs, 13 missense variants that impact SorLA protein trafficking in in vitro cellular assays, and 17 variants with no detectable effect on SorLA protein trafficking. We measured amounts of cleaved sSorLA by western blot in CSF samples. Results We found significantly decreased levels of sSorLA in ADSORL1 TD, compared to all other groups. According to ROC curve analysis, levels of sSorLA showed good performances to distinguish ADSORL1 TD patients from other AD patients (AUC=0.89 [95%CI: 0.81-0.97]). Conclusions Our results suggest that differential levels of sSorLA in CSF could be used as a novel marker to explore disrupted trafficking of SorLA protein in Alzheimer disease. This could help solve some proportion of variants of uncertain significance in SORL1.